New optical transition, structural, and ferromagnetic properties of InCrP:Zn implanted with Cr - Shon, Yoon; Lee, J. W.; Lee, D. J.; Yoon, I. T.; Kwon, Y. H.; Kim, H. S.; Kang, T. W.; Kyhm, J. H.; Song, J. D.; Koo, H. C.; Fu, D. J.; Park, C. S.; et al. (ELSEVIER SCIENCE BV, 2014)
InCrP:Zn was prepared using the implantation with Cr concentrations of 0.3% and 0.7%, respectively. It was confirmed that the photoluminescence peaks near 0.85(D, Cr) eV and 0.96(e,Cr) eV were Cr-correlated PL bands by the implantation of Cr. Especially, each 0.85(D, Cr) eV and 0.96(e,Cr) eV peaks were separately observed based on InP. In triple-axis x-ray diffraction patterns, the samples revealed a shoulder peak indicative of intrinsic InCrP. Ferromagnetic hysteresis loops measured at 10 K and 300 K were observed and the temperature-dependent magnetization showed ferromagnetic behavior >= 300 K, which reveals obvious and enhanced ferromagnetic spin coupling mediated by hole. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: SEMICONDUCTORS; INP; GAAS; MN